British Dietetic Association evidence‐based guidelines for the protein requirements of adults undergoing maintenance haemodialysis or peritoneal dialysis. Issue 4 (4th June 2013) - Naylor, H. L.; Jackson, H.; Walker, G. H.; Macafee, S.; Magee, K.; Hooper, L.; Stewart, L.; MacLaughlin, H. L.; ,
Abstract: Background: Existing nutritional guidelines suggest that protein requirements of adults with stage five chronic kidney disease undergoing haemodialysis (HD) or peritoneal dialysis (PD) are increased as a result of protein losses during dialysis. The present review aimed to update previous guidance and develop evidence‐based practice guidelines on the protein requirements of adults undergoing maintenance dialysis. Methods: Following a PICO approach (Participants or Population, Intervention or Exposure, Comparison and Outcome), four research questions were formulated to investigate the total protein requirement and protein quality required by adults undergoing HD and PD. A comprehensive, systematic review was undertaken using the databases Medline, EMBASE and the Cochrane Library from 2005 to September 2009 for HD studies and from 1997 to September 2009 for PD studies. Results: The literature search yielded 2931 studies, which were assessed for inclusion. Following appraisal, 19 studies in HD and 18 studies in PD met the inclusion criteria and were systematically reviewed. Limited good quality evidence supports the recommendations that: (i) adults undergoing maintenance HD require a minimum protein intake of 1.1 g kg −1 ideal body weight (IBW) per day; and (ii) adults undergoing maintenance PD require a minimum protein intake of 1.0–1.2 kg −1 IBW per day, in conjunction with an adequate energy intake. There were no studies that addressed the quality of protein for either HD or PD. Conclusions: Evidence suggests that nutritional status may be maintained with lower protein intakes than previously recommended. However, the evidence base is limited and further randomised controlled trials are required to establish the optimal protein intake for dialysis patients.